The Use of Platelet-Rich Fibrin in the Treatment of Burn Wounds: A Literature Review - Szymański, Łukasz; Gołąbek, Natalia; Mordarska, Milena; Kodura, Alicja; Piwowarczyk, Alicja; Łozowski, Jan; Paluchowska, Joanna; Białas, Julia; Merc, Artur; Piątek, Przemysław (Quality in Sport, 2026)
Background. Platelet-rich fibrin (PRF) is an autologous fibrin-based biomaterial prepared from the patient’s blood by centrifugation. After tissue injury, such as a burn, platelets become activated and accumulate within the wound site, where they release chemokines, cytokines, and growth factors that are essential for regulating and supporting the wound healing process [1]. Aim. In this literature review, we summarize the available evidence regarding the use of PRF in burn wound management. Materials and methods. A literature search was conducted in PubMed and Google Scholar using combinations of the keywords “platelet-rich fibrin” and “burn wounds”. English-language meta-analyses, systematic reviews, clinical trials, original studies, case series, and case reports were screened without date restrictions, and studies reporting human data on PRF use in burn wound healing were included. Reference lists of eligible articles were also manually reviewed. Results. The available literature suggests that platelet-rich fibrin may influence burn wound healing, indicating its potential as a beneficial adjunct in burn wound management. Conclusions. PRF appears to be a promising adjunct in burn wound management. However, further well-designed studies are required to establish standardized protocols and confirm efficacy.